Base fabric for airbag

By using a urethane resin composition with excellent adhesion on the base fabric for airbags, the problems of high airtightness and good packability under low coating amount are solved, and the softness and light weight of the base fabric for airbags are achieved, meeting the requirements for airbag use.

CN119332510APending Publication Date: 2025-01-21ASAHI KASEI KOGYO KABUSHIKI KAISHA +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410958713.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve both high airtightness and good packability on the base fabric of airbags with a low coating amount. Furthermore, the use of coating materials causes the base fabric to harden and increase in weight, affecting its lightweight and packability.

Method used

Using urethane resin with excellent adhesion as the coating material, an aqueous urethane resin composition is formed by reacting urethane resin with polyisocyanate, branched polycarbonate diol and a compound with anionic hydrophilic groups, and then coating it onto a base fabric at an amount of 5 g/m2 to 15 g/m2 to form a base fabric for airbags.

Benefits of technology

It achieves high airtightness and good packability of airbag base fabric with low coating amount, while maintaining the softness and light weight of base fabric to meet the requirements of airbag use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004949659260000231
    Figure BDA0004949659260000231
  • Figure BDA0004949659260000241
    Figure BDA0004949659260000241
  • Figure BDA0004949659260000251
    Figure BDA0004949659260000251
Patent Text Reader

Abstract

Provided is a base fabric for an airbag in which a coating material is disposed, the base fabric being capable of achieving high airtightness and storability even if the coating amount is small. A base fabric for an airbag, the base fabric comprising a base fabric and a cured product of an aqueous urethane resin composition coated on at least one surface of the base fabric, the base fabric being characterized in that the aqueous urethane resin composition contains a urethane resin, the urethane resin is obtained by reacting (d) a polyamine having two or more amino groups and / or imino groups with an isocyanate group-terminated prepolymer. And an isocyanate group-terminated prepolymer which is obtained by reacting (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms as essential components, and which is coated with a cured product of the aqueous urethane resin composition at a ratio of 5-15 g / m2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a base fabric for an airbag. More specifically, the present invention relates to a base fabric for an airbag that can improve airtightness and storage properties even with a small coating amount by using a urethane resin having excellent adhesion as a coating material. Background Art

[0002] Airbags reduce the impact of collisions and the contact between vehicle interior parts and the human body during accidents. For this reason, airbags are required to be airtight. In addition, airbags are often deployed using inflators that use gunpowder, and the base fabric used in airbags is required to have high heat resistance in order to withstand the high-temperature gas and residues generated. In order to solve these problems, a method of configuring a coating material on the surface of the base fabric used in airbags is widely used for the purpose of improving airtightness and heat resistance.

[0003] As a trend nowadays, the number of airbag mounting locations is increasing due to the improvement of safety standards worldwide, and the airbag itself is becoming larger in size to expand the protection range. On the other hand, the storage space for airbags is limited due to the expansion of the living space of the vehicle, and there is a strong demand for lightweight components used in vehicles in order to help improve fuel consumption. In order to meet these requirements, high storage performance and light weight are listed as important items, and a base fabric with good storage performance and light weight is required while configuring the coating material.

[0004] Patent Document 1 listed below discloses a base fabric for an airbag, which reduces the weight of the bag body by using a urethane resin instead of a silicone resin widely used in a coating material for an airbag.

[0005] Patent Document 2 listed below discloses a base fabric for an air bag that has high slip resistance and a small folded thickness by using a urethane resin as a coating material.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-168131

[0009] Patent Document 2: Japanese Patent Application Publication No. 2009-62643 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] The coating material disposed on the airbag base fabric plays the role of improving air tightness and heat resistance. Generally speaking, the coating amount is proportional to these properties. In order to meet the air tightness and heat resistance required for the airbag base fabric, it is necessary to apply a coating material of a prescribed amount or more. On the other hand, if the base fabric becomes thicker due to the coating material, the rigidity of the coating material is applied to the base fabric, the base fabric becomes hard, and the storage property deteriorates. On this basis, there is a problem that the weight of the base fabric increases and the lightness deteriorates due to the weight of the coating material. It is hoped that a base fabric that can meet the required standards of the base fabric and improve the storage property and lightness can be developed.

[0012] Patent Document 1 discloses a method of satisfying the airtightness of a base fabric by using a coating material having excellent adhesion to the base fabric even with a small coating amount. However, the method only evaluates the air permeability at a low pressure of 125 Pa, and does not disclose the air permeability at a high pressure of 50 kPa or more required for the base fabric of an airbag. In addition, the examples disclose only the air permeability of 20 g / m 2 The results of the study are as follows: whether it is possible to 2 There is no disclosure that high airtightness can be achieved with a coating amount of , and there is still room for improvement in terms of maintaining airtightness at a low coating amount and a high pressure.

[0013] Patent Document 2 below discloses a method of providing a lightweight and soft base fabric by using a coating material with high slip resistance, but only performs an evaluation of air permeability at a low pressure of 125 Pa, and does not disclose air permeability at a high pressure of 50 kPa or more required for the base fabric of an airbag. In addition, there is still room for improvement in slip resistance.

[0014] In view of the level of the prior art, an object of the present invention is to provide an airbag base fabric on which a coating material is disposed, which can achieve high airtightness and storage properties even with a small coating amount.

[0015] Solutions for solving problems

[0016] As a result of intensive studies to solve the above problems, the present inventors unexpectedly found that the airtightness and storage properties of the base fabric for an airbag can be improved even with a small coating amount by using a urethane resin having excellent adhesion as a coating material, thereby completing the present invention.

[0017] That is, the present invention is as follows.

[0018] [1] A base fabric for an airbag, comprising a base fabric and a cured product of an aqueous urethane resin composition applied to at least one surface of the base fabric, wherein the aqueous urethane resin composition comprises a urethane resin obtained by reacting (d) a polyamine having two or more amino groups and / or imino groups with an isocyanate group-terminated prepolymer, wherein the isocyanate group-terminated prepolymer comprises (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms as essential components.

[0019] 5g / m 2 ~15g / m 2 A cured product of the aqueous urethane resin composition is applied.

[0020] [2] The base fabric for an airbag according to [1], wherein the (b) branched polycarbonate diol has a structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms.

[0021] [3] The base fabric for an airbag according to [1] or [2], wherein the polycarbonate diol (b) having a branched structure has a structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms and a structural unit derived from a diol having a linear structure and having 3 to 10 carbon atoms.

[0022] [4] A base fabric for an air bag according to any one of [1] to [3] above, wherein the aqueous urethane resin composition comprises a urethane resin obtained by reacting the aforementioned (d) with an isocyanate-terminated prepolymer, wherein the isocyanate-terminated prepolymer is obtained by reacting the aforementioned (a), (b) and (c) with (e) a trivalent or higher alcohol as an essential component.

[0023] [5] The base fabric for an airbag according to any one of [1] to [4] above, wherein the base fabric for an airbag has a slip resistance of 1000N to 2500N.

[0024] [6] The airbag base fabric according to any one of [1] to [5], wherein the airbag base fabric has an air permeability of 0.01 l / cm2 at a pressure difference of 100 kPa. 2 / min or less.

[0025] [7] The base fabric for an airbag according to any one of [1] to [6], wherein the base fabric for an airbag is composed of a raw yarn having a fineness of 200 dtex to 800 dtex.

[0026] [8] The base fabric for an air bag according to any one of [1] to [7], wherein the fiber constituting the base fabric is polyethylene terephthalate fiber or polyhexamethylene adipamide fiber.

[0027] [9] The base fabric for air bags according to any one of [1] to [8], wherein the tensile strength of the fibers constituting the base fabric is 7.5 cN / dtex to 11.5 cN / dtex.

[0028]

[10] The base fabric for an airbag according to any one of [1] to [9], wherein the weight of the remainder after removing the cured product of the aqueous urethane resin composition is 150 g / m 2 ~300g / m 2 .

[0029] Effects of the Invention

[0030] The base fabric for an airbag according to the present invention has excellent airtightness and storage properties even when the coating material is applied in a low amount. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a method of folding a base fabric in the storage performance evaluation in the embodiment of the present application. DETAILED DESCRIPTION

[0032] Hereinafter, embodiments of the present invention will be described in detail.

[0033] One embodiment of the present invention is a base fabric for an airbag, which is a base fabric for an airbag, comprising a base fabric and a cured product of an aqueous urethane resin composition applied to at least one surface of the base fabric, characterized in that the aqueous urethane resin composition comprises a urethane resin, the urethane resin is obtained by reacting (d) a polyamine having two or more amino groups and / or imino groups with an isocyanate-terminated prepolymer, the isocyanate-terminated prepolymer comprising (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms as essential components and reacting them.

[0034] 5g / m 2 ~15g / m 2 A cured product of the aqueous urethane resin composition is applied.

[0035] The "water-based" of the aqueous urethane resin composition applied to the airbag base fabric of the present embodiment means that after the urethane resin is emulsified and dispersed in water to prepare an emulsified dispersion having a resin component concentration of 40% by mass in water, the emulsified dispersion can be left standing at 20° C. for 12 hours without separation or sedimentation. In the present embodiment, the aqueous urethane resin composition is applied to the base fabric and cured to form a coating material.

[0036] The (a) polyisocyanate component used as the urethane resin applied to the airbag base fabric of the present embodiment is not particularly limited, and aromatic, aliphatic and alicyclic polyisocyanates commonly used in the past can be used. Specifically, as the aromatic polyisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 3,3'-dichloro-4,4'-biphenylene diisocyanate, 1,5-naphthalene diisocyanate, toluidine diisocyanate, tetramethylene xylylene diisocyanate, xylylene diisocyanate, etc. can be used. As aliphatic polyisocyanates, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, etc. can be used; as alicyclic polyisocyanates, isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate, norbornane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, etc. can be used.

[0037] These polyisocyanates may be used alone or in combination of two or more. From the viewpoint of the non-yellowing property of the obtained urethane resin, aliphatic polyisocyanates and alicyclic polyisocyanates are preferred.

[0038] The (b) branched polycarbonate diol component used in the urethane resin applied to the airbag base fabric of the present embodiment is a compound obtained by 1) reaction of a diol component with a chlorocarboxylic acid, 2) reaction of a diol component with phosgene, 3) reaction of a diol component with a cyclic carbonate, 4) condensation reaction of a dicarbonate compound, etc., and has a structural unit derived from a diol having a branched structure. The (b) branched polycarbonate diol component used in the urethane resin applied to the airbag base fabric of the present embodiment may be a structural unit derived from a diol having a branched structure alone or may contain a structural unit derived from a diol having a linear structure. It is more preferred to have a structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms, and it is most preferred to have a structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms and a structural unit derived from a diol having a linear structure and having 3 to 10 carbon atoms. As the structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl-1,8-octanediol, neopentyl glycol, etc. can be used. As the structural unit derived from a diol having a straight-chain structure and having 3 to 10 carbon atoms, 1,10-decanediol, 1,9-nonanediol, 1,8-octanediol, 1,6-hexanediol, 1,5-pentanediol, 1,4-butanediol, 1,3-propanediol, etc. can be used.

[0039] In addition, the number average molecular weight of the polycarbonate diol component (b) having a branched structure used as the urethane resin applied to the airbag base fabric of the present embodiment is preferably 500 to 6000, more preferably 800 to 4000. When the number average molecular weight is above the lower limit, the airbag base fabric has excellent slip resistance and storage properties, while when it is below the upper limit, the airbag base fabric has excellent air permeability.

[0040] The ratio of (b) to the total mass of the compound having a hydroxyl group capable of reacting with the isocyanate group in the urethane resin is preferably 10 to 99.7 mass %, more preferably 30 to 99.6 mass % from the viewpoint of the slip resistance and storage property of the airbag base fabric. If the ratio of (b) is greater than the above lower limit, the slip resistance and storage property of the airbag base fabric are excellent.

[0041] The compound having a hydroxyl group that can react with an isocyanate group refers to (b), diols other than (b) described later, (c) and (e).

[0042] From the viewpoint of the slip resistance, air permeability and storage properties of the base fabric for an airbag, the structural unit derived from the diol having a branched structure in the structural unit derived from the diol (b) is preferably 10 to 100 mol %, more preferably 30 to 100 mol %.

[0043] As the diol other than (b) contained when the ratio of (b) is less than 99.7 mass %, diols such as polyether diols, polyester diols, polycarbonate diols other than (b), and diols having a number average molecular weight of 200 or less can be used.

[0044] As the polyether diol, polymers of alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide can be used. Such a polymer can be a homopolymer of one alkylene oxide, or a copolymer of two or more alkylene oxides. In the case of a copolymer, it can be a random polymer or a block polymer. In addition, the number average molecular weight of such a polyether diol is preferably 400 to 5000. In addition, as the aforementioned polyether diol, a compound obtained by adding one or more alkylene oxides to a diol having a number average molecular weight of 200 or less can also be used. As the aforementioned diol having a number average molecular weight of 200 or less, ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, nonanediol, neopentyl glycol, etc. can be used.

[0045] As the polyester diol, there can be used a diol component such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol having a number average molecular weight of 300 to 1,000, dipropylene glycol, tripropylene glycol, bishydroxyethoxybenzene, 1,4-cyclohexanedimethanol, bisphenol A, bisphenol S, hydrogenated bisphenol A, hydroquinone or their alkylene oxide adducts and a dimer acid, succinic acid, adipic acid, azelaic acid, Polyester diols obtained by dehydration condensation reaction of dicarboxylic acid components such as sebacic acid, dodecanedicarboxylic acid, maleic anhydride, fumaric acid, 1,3-cyclopentanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalenedicarboxylic acid, biphenyldicarboxylic acid, 1,2-bisphenoxyethane-p,p'-dicarboxylic acid, anhydrides or ester-forming derivatives of dicarboxylic acids; polyester diols obtained by ring-opening polymerization of cyclic ester compounds such as ε-caprolactone; polyester diols obtained by copolymerizing these, etc.

[0046] As the polycarbonate diol other than (b), there can be used polycarbonate diols obtained by reaction of one or more diols selected from diols such as 1,10-decanediol, 1,9-nonanediol, 1,8-octanediol, 1,6-hexanediol, 1,5-pentanediol, 1,4-butanediol, 1,3-propylene glycol, and diethylene glycol with chlorocarboxylic acids, phosgene, cyclic carbonates, or the like, or condensation reaction of dicarbonate compounds.

[0047] As the diol having a number average molecular weight of 200 or less, ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, nonanediol, neopentyl glycol, and the like can be used.

[0048] These diols other than (b) may be used alone or in combination of two or more.

[0049] (b) As polycarbonate diols having a branched structure, there are the following, for example.

[0050] · Polycarbonate diols derived from 3-methyl-1,5-pentanediol / 1,6-hexanediol (Kuraray Polyol C-1090 (number average molecular weight: 1000), Kuraray Polyol C-2090 (number average molecular weight: 2000), Kuraray Polyol C-3090 (number average molecular weight: 3000), Kuraray Polyol C-5090 (number average molecular weight: 5000) manufactured by Kuraray Corporation).

[0051] Polycarbonate diol derived from 2-methyl-1,3-propanediol (ETERNACOLL UP-100 (number average molecular weight: 1000), ETERNACOLL UP-200 (number average molecular weight: 2000) manufactured by UBE).

[0052] Polycarbonate diols derived from 2-methyl-1,8-octanediol / 1,9-nonanediol (Kuraray Polyol C-1015N (number average molecular weight: 1000), Kuraray Polyol C-2015N (number average molecular weight: 2000), Kuraray Polyol C-1065N (number average molecular weight: 1000), Kuraray Polyol C-2065N (number average molecular weight: 2000) manufactured by Kuraray Corporation).

[0053] · Polycarbonate diol derived from 2,2-dimethyl-1,3-propanediol (BENEBiOL NL1005B (number average molecular weight: 1000), BENEBiOL NL2005B (number average molecular weight: 2000), BENEBiOL NL1030B (number average molecular weight: 1000), BENEBiOL NL2030B (number average molecular weight: 2000, manufactured by Mitsubishi Chemical Corporation)

[0054] The (c) compound having an anionic hydrophilic group and at least two active hydrogen atoms used in the urethane resin applied to the airbag base fabric of the present embodiment refers to a compound having an anionic hydrophilic group such as a carboxyl group, a carboxylate group, a sulfonic group, a sulfonate group, and a group containing active hydrogen atoms such as two or more hydroxyl groups. Specifically, 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolpentanoic acid, dihydroxymaleic acid, 2,6-dihydroxybenzoic acid, etc. can be used. By copolymerizing the (c) compound having an anionic hydrophilic group and at least two active hydrogen atoms, a self-emulsifying urethane resin can be obtained.

[0055] The content of the anionic hydrophilic group in the urethane resin is preferably 0.3 to 3% by mass, and more preferably 0.5 to 2.5% by mass, from the viewpoint of emulsification stability and storage stability. If the content of the anionic hydrophilic group is above the aforementioned lower limit, there is a tendency that the emulsification stability and storage stability of the urethane resin are excellent, and the urethane resin can be used stably. On the other hand, if it is below the aforementioned upper limit, the softness of the urethane resin is excellent, and the slip resistance and storage property of the base fabric for the airbag are improved.

[0056] As the polyamine (d) having two or more amino groups and / or imino groups used for the urethane resin applied to the airbag base fabric of the present embodiment, diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, hexamethylenediamine, diaminocyclohexylmethane, hydrazine, 2-methylpiperazine, isophoronediamine, norbornanediamine, diaminodiphenylmethane, toluenediamine, and xylenediamine; and polyamines such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and iminobispropylamine can be used. ; Amidoamine derived from a diprimary amine and a monocarboxylic acid; water-soluble amine derivatives such as monoketimine of a diprimary amine; hydrazine derivatives such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, sebacic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, itaconic acid dihydrazide, 1,1'-vinylhydrazide, 1,1'-trimethylenehydrazide, 1,1'-(1,4-butene) dihydrazide, etc. These polyamines may be used alone or in combination of two or more.

[0057] The amount of (d) used is preferably an amount containing 0.6 to 1.2 equivalents of amino groups and the like relative to the free isocyanate groups of the isocyanate group-terminated prepolymer described below.

[0058] The urethane resin coated on the airbag base fabric of this embodiment is obtained by reacting the aforementioned (d) with an isocyanate-terminated prepolymer, wherein the isocyanate-terminated prepolymer is obtained by reacting the aforementioned (a), (b) and (c) as essential components, and is usually obtained in the form of a water dispersion.

[0059] (isocyanate-terminated prepolymer)

[0060] In the production of the isocyanate group-terminated prepolymer, a diol other than (b) may be used in combination, and (e) a trivalent or higher alcohol component may also be used in combination.

[0061] As the (e) trivalent or higher alcohol, trimethylolpropane, pentaerythritol, sorbitol, etc. can be used.

[0062] Compounds having a number average molecular weight of 500 or less obtained by adding one or more alkylene oxides to polyalkylene polyamines or the above-mentioned trivalent or higher alcohols can also be used as (e). Examples of polyalkylene polyamines include ethylenediamine, diethylenetriamine, triethylenetetramine, and the like. As the above-mentioned alkylene oxides, alkylene oxides having 1 to 4 carbon atoms (specifically, ethylene oxide, propylene oxide, butylene oxide, and the like) can be used.

[0063] Among the trivalent or higher alcohols, trivalent to tetravalent alcohols are preferred, and trivalent alcohols are more preferred, from the viewpoint of the folding performance of the base fabric for an airbag.

[0064] The ratio of the mass of (e) to the total mass of the compound having a hydroxyl group capable of reacting with an isocyanate group, i.e., (b), the diol other than (b), (c) and (e) is preferably 0.1 to 5 mass %, more preferably 0.3 to 3 mass %, from the viewpoint of the slip resistance, air permeability and storage property of the airbag.

[0065] When the ratio of (e) is not less than the aforementioned lower limit, the airbag base fabric has excellent air permeability, while when it is not more than the aforementioned upper limit, the airbag base fabric has excellent slip resistance and stowability.

[0066] The method for producing the isocyanate group-terminated prepolymer is not particularly limited, and a conventionally known one-step so-called one-shot process, a multi-step isocyanate polyaddition reaction method, or the like can be used.

[0067] The reaction temperature is preferably 40 to 150° C. At this time, a reaction catalyst such as dibutyltin dilaurate, stannous octoate, dibutyltin di(2-ethylhexanoate), triethylamine, triethylenediamine, N-methylmorpholine, bismuth tri(2-ethylhexanoate), diazabicycloundecene, or a reaction inhibitor such as phosphoric acid, sodium hydrogen phosphate, p-toluenesulfonic acid, adipic acid, benzoyl chloride, etc. may be added as needed.

[0068] During or after the reaction, an organic solvent that does not react with an isocyanate group may be added. Examples of such organic solvents include acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, dioxane, dimethylformamide, dimethyl sulfoxide, toluene, xylene, ethyl acetate, butyl acetate, and dichloromethane. Among these organic solvents, methyl ethyl ketone, toluene, and ethyl acetate are particularly preferred. In addition, these organic solvents may be removed by heating and reducing pressure after emulsification, dispersion, and chain extension of the prepolymer.

[0069] When producing an isocyanate-terminated prepolymer, the molar ratio of the isocyanate group to the hydroxyl group of the raw material in the non-volatile component of the prepolymer (NCO / OH) is preferably 1.1 to 2, more preferably 1.25 to 1.7. By adjusting the molar ratio of the isocyanate group to the hydroxyl group of the raw material to within the above range, an isocyanate-terminated prepolymer having a desired free isocyanate group content can be obtained.

[0070] The content of free isocyanate groups in the isocyanate-terminated prepolymer is preferably 0.2 to 5% by mass, and more preferably 1 to 4% by mass. If the free isocyanate group content is above the lower limit, the isocyanate-terminated prepolymer exhibits an appropriate viscosity during production, so the amount of organic solvent used can be suppressed and sufficient emulsification and dispersion can be performed. On the other hand, if the free isocyanate group content is below the upper limit, the balance change of water solubility after emulsification and dispersion and after chain extension based on (d) polyamine is small, and the storage stability or processing stability over time of the urethane resin is excellent.

[0071] (a) polyisocyanate, (b) polycarbonate diol having a branched structure, (c) a compound having an anionic hydrophilic group and at least 2 active hydrogen atoms, and (e) trivalent or higher alcohol all have multiple reaction sites, and the isocyanate-terminated prepolymer obtained by reacting them has a complex structure and cannot be directly represented by a general formula (structural formula).

[0072] (Neutralized product of isocyanate-terminated prepolymer)

[0073] The neutralized product of the isocyanate group-terminated prepolymer is obtained by neutralizing the anionic hydrophilic groups in the isocyanate group-terminated prepolymer.

[0074] The neutralized product of the isocyanate group-terminated prepolymer (i) can be produced by neutralizing the anionic hydrophilic group in the isocyanate group-terminated prepolymer by a known method, or (ii) can be produced by mixing (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms, and (d) a trivalent or higher alcohol, neutralizing the anionic hydrophilic group of the compound having anionic hydrophilic group and at least two active hydrogen atoms (c) by a known method, and then reacting the neutralized (c) compound having anionic hydrophilic group and at least two active hydrogen atoms, (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (e) the trivalent or higher alcohol. Alternatively, (iii) can be produced by reacting (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms, wherein the anionic hydrophilic group of the compound is a salt of an anionic hydrophilic group, that is, (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms, and (e) a trivalent or higher alcohol.

[0075] In the production methods (i) and (ii), the basic compound used for neutralization of the anionic hydrophilic group is not particularly limited, and examples thereof include amines such as trimethylamine, triethylamine, tri-n-propylamine, tributylamine, N-methyl-diethanolamine, N,N-dimethylmonoethanolamine, N,N-diethylmonoethanolamine, and triethanolamine; alkali metal hydroxides such as potassium hydroxide and sodium hydroxide; ammonia, etc. Among these, tertiary amines such as trimethylamine, triethylamine, tri-n-propylamine, and tributylamine are particularly preferred.

[0076] In the neutralization of the anionic hydrophilic group in the manufacturing methods (i) and (ii), the amount of the neutralizing alkaline compound used is preferably 0.5 to 1.5 equivalents, more preferably 0.6 to 1.4 equivalents, and particularly preferably 0.7 to 1.3 equivalents relative to the anionic hydrophilic group. If the amount of the neutralizing alkaline compound used is less than the lower limit, the emulsification and storage stability of the carbamate resin tend to decrease. On the other hand, even if the amount of the neutralizing alkaline compound exceeding the upper limit is added, the emulsification and storage stability of the carbamate resin will not be further improved, and therefore, it is not preferred from an economic point of view.

[0077] (Urethane resin)

[0078] In the present specification, the urethane resin refers to a resin (chain-extended product) obtained by chain-extending the neutralized product of the isocyanate group-terminated prepolymer using (d) a polyamine.

[0079] (Emulsification and dispersion)

[0080] When the neutralized isocyanate-terminated prepolymer is extended, first, the neutralized isocyanate-terminated prepolymer is emulsified and dispersed in water. The method of emulsification and dispersion is not particularly limited, and existing known methods using a homogenizer, a homogenizer, a disperser, etc. can be cited. In particular, even without adding an emulsifier, it can be emulsified and dispersed in water at a temperature within the range of 0 to 40° C., which can inhibit the reaction of the isocyanate group with water. When emulsifying and dispersing it, a reaction inhibitor such as phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, p-toluenesulfonic acid, adipic acid, benzoyl chloride, etc. can be added as needed.

[0081] (Chain Extension)

[0082] Next, the aforementioned neutralized isocyanate-terminated prepolymer emulsified and dispersed in water is chain extended using (d) polyamine to form the urethane resin of the present invention. The chain extension method is not particularly limited, but preferably: a method of adding (d) polyamine to the emulsified dispersion of the neutralized isocyanate-terminated prepolymer to extend the chain; or a method of adding the emulsified dispersion of the neutralized isocyanate-terminated prepolymer to (d) polyamine to extend the chain. Regarding the reaction of the neutralized isocyanate-terminated prepolymer with the amine, the reaction is usually completed within 30 to 120 minutes after the neutralized isocyanate-terminated prepolymer and the (d) polyamine are mixed at a reaction temperature of 20 to 50°C.

[0083] Chain extension may be performed simultaneously with emulsification and dispersion, after emulsification and dispersion, or before emulsification and dispersion. When the obtained urethane resin contains an organic solvent, it is preferred to remove the organic solvent at a temperature of 30 to 80° C. under reduced pressure.

[0084] Similar to (a) polyisocyanate, (b) polycarbonate diol having a branched structure, (c) compound having an anionic hydrophilic group and at least two active hydrogen atoms, and (e) trivalent or higher alcohol, (d) polyamine also has a plurality of reaction sites. The chain extension product (urethane resin) of the neutralized isocyanate-terminated prepolymer obtained by chain extension of the neutralized isocyanate-terminated prepolymer using the (d) polyamine also has a complex structure like the isocyanate-terminated prepolymer and cannot be directly represented by a general formula (structural formula).

[0085] The urethane resin thus obtained is preferably used in a state of being emulsified and dispersed in water, and its resin component concentration is not particularly limited, but is preferably 20 to 60% by mass. The resin component concentration in the aqueous emulsified dispersion of the urethane resin can be adjusted by adding or removing water.

[0086] From the perspective of the slip resistance, air permeability and storage properties of the base fabric for airbags, the aqueous urethane resin composition applied to the base fabric for airbags of this embodiment can be blended with other resins (for example, urethane resins other than the urethane resin of the present invention, acrylic resins, polyester resins, etc.), thickeners, cross-linking agents, surfactants, defoamers, leveling agents, viscoelasticity regulators, wetting agents, dispersants, preservatives, film-forming agents, plasticizers, penetrants, fragrances, bactericides, miticides, mildewicides, ultraviolet absorbers, antioxidants, antistatic agents, flame retardants, dyes, pigments and other additives within the range that does not impair the effects of the present invention.

[0087] The content of the urethane resin in the solid content of the aqueous urethane resin composition is preferably 20 to 100% by mass, and more preferably 40 to 100% by mass, from the viewpoint of the slip resistance, air permeability, and storage property of the airbag base fabric. When it is 20% by mass or more, the slip resistance, air permeability, and storage property of the airbag base fabric are excellent.

[0088] When determining the solid content in the aqueous urethane resin composition before applying to the base fabric, the solid content can be calculated by measuring the mass of the remainder when 5 g of the aqueous urethane resin composition is dried at 100±5° C. for 3 hours.

[0089] As resins other than carbamate resins, acrylic resins can be cited. As acrylic monomers used in acrylic resins, (meth) methyl acrylate, (meth) ethyl acrylate, (meth) 2-ethylhexyl acrylate, (meth) lauryl acrylate, (meth) stearyl acrylate, (meth) cyclohexyl acrylate, (meth) isobornyl acrylate, (meth) benzyl acrylate, (meth) acrylic acid, (meth) glycidyl acrylate, (meth) dimethylaminoethyl acrylate, (meth) diethylaminoethyl acrylate, (meth) 2-hydroxyethyl acrylate, (meth) 2-hydroxypropyl acrylate and other (meth) acrylic acid derivatives can be cited. Here, (meth) acrylic acid represents acrylic acid or methacrylic acid. In addition, these acrylic monomers can be used alone or in combination of two or more.

[0090] Examples of the comonomers used in the acrylic resin include aromatic vinyl compounds such as styrene, α-methylstyrene, and p-methylstyrene; acrylamides such as acrylamide, diacetone acrylamide, methacrylamide, and maleic acid amide; heterocyclic vinyl compounds such as vinyl pyrrolidone; vinyl compounds such as vinyl chloride, acrylonitrile, vinyl ether, vinyl ketone, and vinyl amide; α-olefins such as ethylene and propylene; maleic acid, fumaric acid, itaconic acid, and their derivatives, etc. These comonomers may be used alone or in combination of two or more.

[0091] In order to adjust the aqueous urethane resin composition to an appropriate viscosity, a thickener may be blended. Examples of such thickeners include alkali thickening type acrylic resins, associative thickeners, and water-soluble organic polymers. These thickeners may be used alone or in combination of two or more.

[0092] As the alkali thickening type acrylic resin, a commercially available product can be used. Usable are NIKASOL VT-253A (manufactured by Nippon Carbide Industries); ARON A-20P, ARON A-7150, ARON A-7070, ARON B-300, ARON B-300K, ARON B-500 (manufactured by Toagosei Co., Ltd.); JURIMER AC-10LHP, JURIMER AC-10SHP, RHEOZIC 835H, JUNRON PW-110, JUNRON PW-150 (manufactured by Nippon Junyaku Co., Ltd.); PRIMALASE-60, PRIMAL TT-615, PRIMAL RM-5 (manufactured by Rohm & Haas, Japan); SN THICKENER A-818, SN THICKENER A-850 (manufactured by San Nopco); PARAGUM 500 (manufactured by Para-Chem Southern); RHEOLATE 430 (manufactured by Elementis NEOSTECKER V-420 (manufactured by Nikka Chemical Co., Ltd.), etc. Such alkali-thickened acrylic resins are generally sold in the form of emulsified dispersions of the resins, and are preferably used in the state of emulsified dispersion.

[0093] As the associative thickener, commercially available products can be used. As commercially available associative thickeners, ADEKANOL UH-450, ADEKANOL UH-450VF, SN THICKENER 621N, SN THICKENER 623N, SN THICKENER 660T (all manufactured by San Nopco); RHEOLATE 244, RHEOLATE 278, RHEOLATE 300 (all manufactured by Elementis Japan); DK THICKENER SCT-275 (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.); NEOSTECKER N-5400 (manufactured by Nichika Chemical Co., Ltd.) and the like can be used.

[0094] As water-soluble organic polymers, natural water-soluble organic polymers, semi-synthetic water-soluble organic polymers, and synthetic water-soluble organic polymers can be listed. As the aforementioned natural water-soluble organic polymers, starches such as potato starch, sweet potato starch, wheat starch, rice starch, cassava starch, and corn starch can be used; resin polysaccharides such as gum arabic, tragacanth gum, karaya gum, and okra root (TOROROAOI); seaweed polysaccharides such as sodium alginate, carrageenan, agar (galactan), and nori; microbial fermentation polysaccharides such as xanthan gum, pullulan, thermogel, dextrin, and fructan; proteins such as casein, gelatin, albumin, glue, and collagen; pectin, chitin, chitosan, etc.

[0095] As semi-synthetic water-soluble organic polymers, cellulose derivatives such as methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, and sodium cellulose sulfate; starch derivatives such as dextrin, soluble starch, oxidized starch, carboxymethyl starch, hydroxyethyl starch, hydroxypropyl starch, dialdehyde starch, phosphate starch, and acetyl starch; propylene glycol alginate, etc. can be used.

[0096] As the synthetic water-soluble organic polymer, polyvinyl alcohol, polyacrylic acid, polyacrylic acid salt, polyacrylamide, polyvinyl pyrrolidone, polyvinyl alkyl ether, maleic anhydride copolymer, maleic acid copolymer, maleate copolymer, etc. can be used.

[0097] The amount of the thickener (the amount of the nonvolatile component) may be appropriately adjusted according to the viscosity of the aqueous urethane resin composition, and is usually preferably 0.1 to 40 parts by mass, more preferably 0.3 to 30 parts by mass, based on 100 parts by mass of the urethane resin.

[0098] The aqueous urethane resin composition may contain a crosslinking agent in order to improve the air permeability of the airbag.

[0099] As the crosslinking agent, a carbodiimide crosslinking agent, an isocyanate crosslinking agent, an epoxy crosslinking agent, an oxazoline crosslinking agent, an aziridine crosslinking agent, a blocked isocyanate crosslinking agent, a water-dispersible isocyanate crosslinking agent, a melamine crosslinking agent, etc. can be used. One of these crosslinking agents can be used alone, or two or more can be used in combination. From the viewpoint of the stability of the working fluid, it is particularly preferred to mix a carbodiimide crosslinking agent.

[0100] As the crosslinking agent, a commercial item can be used. As commercial items of the carbodiimide crosslinking agent, CARBODILITE E-02, CARBODILITE SV-02, CARBODILITE V02-L2, CARBODILITE V-10 (all manufactured by Nisshinbo Chemical Co., Ltd.); NK ASSIST CI-02 (manufactured by Nikka Chemical Co., Ltd.) and the like can be used.

[0101] The amount of the crosslinking agent (the amount of the nonvolatile component) is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 15 parts by mass, based on 100 parts by mass of the urethane resin, from the viewpoint of air permeability of the airbag.

[0102] The fiber used for the base fabric for an air bag of the present embodiment has a thickness of preferably 200 dtex to 800 dtex, more preferably 340 dtex to 600 dtex, and still more preferably 400 dtex to 560 dtex.

[0103] If the fineness of the fiber used is 200 dtex or more, the durability required for the base fabric for airbags can be satisfied, and if it is 800 dtex or less, the base fabric is soft and a base fabric with good storage properties can be produced.

[0104] As the fiber used in the airbag base fabric of the present embodiment, polyethylene terephthalate fiber and polyhexamethylene adipamide fiber can be cited. In addition, in order to improve the productivity or characteristics in the manufacturing process and processing process of the raw yarn, the fiber can contain various commonly used additives. For example, it can contain a heat stabilizer, an antioxidant, a light stabilizer, a smoothing agent, an antistatic agent, a plasticizer, a thickener, a pigment, a flame retardant, etc.

[0105] The (tensile) strength of the fiber used in the airbag base fabric of this embodiment is preferably in the range of 7.5 to 11.5 cN / dtex, more preferably in the range of 8.0 to 11.5 cN / dtex, and particularly preferably in the range of 8.2 to 11.5 cN / dtex. If the strength is 8.0 cN / dtex or more and the greater it is, the more desired mechanical properties can be obtained, which is sufficient as a fiber for industrial materials. In addition, if the strength is 11.5 cN / dtex or less, the fiber quality is excellent, for example, the frequency of burrs is also low, the reduction in spinning yield is suppressed, and weaving failures in post-processing will not be caused.

[0106] The weight of the airbag fabric of the present embodiment after removing the coating material is preferably 150 g / m 2 ~300g / m 2 , more preferably 170g / m 2 ~280g / m 2 , more preferably 175g / m2 ~250g / m 2 , and more preferably 180g / m 2 ~210g / m 2 .

[0107] If the weight of the base fabric after removing the coating material is 150g / m 2 If the thickness is 300 g / m 2 Below, it is possible to produce a lightweight base fabric.

[0108] The slip resistance of the airbag base fabric of this embodiment is preferably 1000N to 2500N, more preferably 1100N to 2000N. If the slip resistance is 1000N or more, the fibers constituting the base fabric are sufficiently strongly restrained, and the fibers are difficult to move even under pressure, so that high air tightness can be obtained. If the slip resistance is 2500N or less, the fibers move appropriately when folded, forming a soft base fabric with good storage properties.

[0109] The air bag base fabric of this embodiment has an air permeability of 0.01 l / cm2 at a pressure difference of 100 kPa. 2 / min or less, preferably 0.008l / cm 2 / min or less.

[0110] The coating amount of the coating material of the airbag base fabric of this embodiment is 5 g / m 2 ~15g / m 2 , preferably 8g / m 2 ~13g / m 2 .

[0111] By setting the coating amount to 5 g / m 2 Above, the airtightness required for the airbag can be satisfied. On the other hand, by 15g / m 2 The following is done to form a base fabric that is light, soft, and has good storage properties.

[0112] Example

[0113] Hereinafter, the present invention will be specifically described by way of Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, each measured value in the Examples was measured by the following method.

[0114] (1) Free isocyanate content

[0115] 0.3 g of urethane prepolymer was taken into a conical flask, and 10 ml of 0.1 N dibutylamine toluene solution was added to dissolve the urethane prepolymer. Then, a few drops of bromophenol blue solution were added, and titrated with 0.1 N hydrochloric acid methanol solution to determine the free isocyanate group content NCO% using the following formula.

[0116] NCO% = (ab) × 0.42 × f / x

[0117] {wherein, a: the titration amount of 0.1N hydrochloric acid-methanol solution when only 10 ml of 0.1N dibutylamine toluene solution is titrated, b: the titration amount of 0.1N hydrochloric acid-methanol solution when a solution in which a urethane prepolymer is dissolved is titrated, f: the factor of 0.1N hydrochloric acid-methanol solution, and x: the amount of urethane prepolymer.}

[0118] (2) Total fineness (dtex)

[0119] The measurement was carried out by the method described in JIS L 1017:2002 8.3.

[0120] (3) (Tensile) strength (cN / dtex)

[0121] The tensile strength was determined by dividing the tensile strength measured by the method described in JIS L 1017:2002 8.5 by the total fineness.

[0122] (4) Slip resistance (N)

[0123] The measurement was carried out according to the method described in ASTM D6479.

[0124] (5) Air permeability (l / cm 2 / min)

[0125] The base fabric was clamped with a 100 mm φ fixture, and pressure was applied to one side of the base fabric. The pressure difference between the two sides of the base fabric was adjusted to 100 kPa, and the air flow rate passing through at this time was measured using a laminar flow tube flowmeter. In addition, 5 locations in the same sample were randomly measured and the average value was calculated.

[0126] (6) Storage

[0127] Based on the following steps:

[0128] 1) Cut the base fabric into 20cm×20cm size;

[0129] 2) The warp direction is made to be the up-down direction, and the coating surface is made to be the upper side;

[0130] 3) Make a valley fold at a distance of 5 cm from the left and right ends of the base fabric and fold it inwards;

[0131] 4) Make a valley fold at a distance of 5 cm from the upper and lower ends of the base fabric and fold it inwards;

[0132] 5) Make a valley fold at a distance of 2.5 cm from the left and right ends of the base fabric and fold it inwards;

[0133] 6) Make a valley fold at a distance of 2.5 cm from the upper and lower ends of the base fabric and fold it inwards;

[0134] 7) Place the sample of 6) above on a flat table, and place a rectangular weight of 2 cm in height, 6 cm in width, 6 cm in depth and 560 g in weight on the sample. Measure the distance from the vertex 4 on the lower surface of the weight to the table, and take the average value of the 4 points as the thickness of the base fabric.

[0135] The thickness of each example and comparative example was measured at 5 random locations, and the average value was calculated as the thickness of each example and comparative example. The thickness of comparative example 1 was set as 100, and the relative value of each example and comparative example was calculated.

[0136] (7) Weight of base fabric (remaining mass) after removing coating material (g / m 2 ) and coating amount (g / m 2 )

[0137] The weight of the base fabric after removing the coating material (remaining amount) is determined by measuring the weight per unit area of ​​the base fabric alone before the coating material is applied, using the method specified in Method 8.3.2 of JIS L-1096:2010.

[0138] The coating amount of the coating material is determined by the method specified in Method 8.3.2 of JIS L-1096:2010 from the difference in weight per unit area of ​​the base fabric before and after the coating of the coating material.

[0139] [Raw materials used in Examples and Comparative Examples]

[0140] <Organic polyisocyanate>

[0141] H12MDI: dicyclohexylmethane 4,4'-diisocyanate ("Desmodur W" manufactured by Covestro).

[0142] ·HDI: Hexamethylene diisocyanate.

[0143] <Polyol>

[0144] T5652: polycarbonate diol manufactured by Asahi Kasei Chemicals Corporation (1,5-pentanediol / 1,6-hexanediol used as raw materials), trade name “DURANOL T5652”, number average molecular weight: 2,000.

[0145] C2090: polycarbonate diol manufactured by Kuraray Co., Ltd. (using 3-methyl-1,5-pentanediol / 1,6-hexanediol as raw materials), trade name “Kuraray Polyol C-2090”, number average molecular weight: 2,000.

[0146] C3090: polycarbonate diol manufactured by Kuraray Co., Ltd. (using 3-methyl-1,5-pentanediol / 1,6-hexanediol as raw materials), trade name “Kuraray Polyol C-3090”, number average molecular weight: 3,000.

[0147] UP200: polycarbonate diol manufactured by UBE (using 2-methyl-1,3-propanediol as a raw material), trade name “ETERNACOLL UP-200”, number average molecular weight: 2,000.

[0148] C2065N: polycarbonate diol manufactured by Kuraray Co., Ltd. (2-methyl-1,8-octanediol / 1,9-nonanediol are used as raw materials), trade name “Kuraray Polyol C-2065N”, number average molecular weight: 2,000.

[0149] <Trivalent or higher polyols>

[0150] ·TMP: trimethylolpropane.

[0151] <Anionic hydrophilic group / active hydrogen containing compound>

[0152] DMPA: dimethylolpropionic acid.

[0153] <Neutralizing Amine>

[0154] ·TEA: triethylamine.

[0155] <Chain Extender>

[0156] Hydrazine monohydrate.

[0157] ·DETA: diethylenetriamine.

[0158] <Thickener>

[0159] ·NEOSTECKER N-5400: Made by Nikka Chemical Co., Ltd.

[0160] <Crosslinking agent>

[0161] NK ASSIST CI-02: Made by Nichika Chemical Co., Ltd.

[0162] <Pigment>

[0163] SA GREEN A4023: Made by Yukoku Pigment Co., Ltd.

[0164] [Example 1]

[0165] (Synthesis example 1)

[0166] Into a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen blowing tube were charged 293.1 parts by mass of a polycarbonate diol (using 2-methyl-1,3-propanediol as a raw material) ("ETERNACOLL UP-200" manufactured by UBE, number average molecular weight: 2,000) as (b) a polycarbonate diol having a branched structure, 12.3 parts by mass of dimethylolpropionic acid as (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms, and 98.7 parts by mass of methyl ethyl ketone, and after uniformly mixing, 89.3 parts by mass of dicyclohexylmethane diisocyanate and 0.099 parts by mass of diazabicycloundecene as (a) a polyisocyanate were added, and the mixture was reacted at 80° C. for 240 minutes to obtain a methyl ethyl ketone solution of an isocyanate-terminated urethane prepolymer having a content of free isocyanate groups of 2.3% by mass relative to the isocyanate-terminated prepolymer. 8.8 parts by mass of triethylamine is added to the solution, and after uniform mixing, 632.7 parts by mass of water is slowly added to emulsify and disperse it. After adding 4.1 parts by mass of hydrazine monohydrate and 1.1 parts by mass of diethylenetriamine as (e) chain extenders to the obtained emulsified dispersion, the mixture is stirred for 90 minutes to obtain a carbamate resin dispersion. Next, the carbamate resin dispersion is desolvated at 40°C under reduced pressure to obtain an aqueous dispersion of a carbamate resin having a resin component of 40.0% by mass. (The proportion of (b) in the total amount of compounds having a hydroxyl group capable of reacting with the isocyanate group in the synthesized carbamate resin, the proportion of the structural unit derived from the diol having a branched structure in the structural unit derived from the (b) diol, and the proportion of (e) in the total amount of compounds having a hydroxyl group capable of reacting with the isocyanate group in the synthesized carbamate resin are recorded in the table in the examples)

[0167] (Aqueous urethane resin composition 1)

[0168] 800 parts by mass of the aqueous dispersion of the urethane resin obtained in Synthesis Example 1, 3.8 parts by mass of a thickener ("NEOSTECKER N-5400" manufactured by Nikka Chemical Co., Ltd.), and 1.6 parts by mass of a pigment ("SA GREEN A4023" manufactured by Mikoku Pigments Co., Ltd.) were mixed to prepare an aqueous urethane resin composition 1.

[0169] Next, the polyhexamethylene adipamide fiber with a total fineness of 470 dtex, 136 monofilaments, and a tensile strength of 8.3 cN / dtex was warped in a twist-free and glue-free form, and the warp yarn was woven into a plain weave using a water jet loom with the same yarn, and then refined and shaped to obtain a base fabric with a weight of 200 g / m 2 Next, the water-based urethane resin composition 1 was applied by knife coating in a coating material coating amount of 11 g / m 2 After coating one side of the base fabric in the form of , the base fabric was treated at 190° C. for 1 minute using a pin tenter heat treatment machine to obtain an airbag base fabric. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.

[0170] [Examples 2 to 9, Comparative Example 1]

[0171] In Synthesis Examples 2 to 7, except that (a) polyisocyanate, (b) polycarbonate diol having a branched structure, (c) a compound having an anionic hydrophilic group and at least two active hydrogens, (d) a polyamine having two or more amino groups and / or imino groups, (e) a trivalent or higher alcohol, and a neutralizing amine were used in the same manner as in Synthesis Example 1, the materials were reacted until the content of free isocyanate groups relative to the isocyanate group-terminated prepolymer was as shown in the table of Examples and Comparative Examples, thereby obtaining an aqueous dispersion of a urethane resin.

[0172] Comparative Synthesis Example 1, Adjustment In Synthesis Example 1, the types and amounts of (a) polyisocyanates, (b) ', polycarbonate diols other than (b), (c) compounds having anionic hydrophilic groups and at least 2 active hydrogens, (d) polyamines having 2 or more amino groups and / or imino groups, (e) trivalent or higher alcohols, and neutralizing amines shown in the tables of Examples and Comparative Examples are used. Except for this, the materials are charged in the same manner as in Synthesis Example 1, and the mixture is reacted until the content of free isocyanate groups relative to the isocyanate group-terminated prepolymer shown in the tables of Examples and Comparative Examples is reached, thereby obtaining an aqueous dispersion of a urethane resin.

[0173] In aqueous urethane resin compositions 2 to 9 and comparative aqueous urethane resin composition 1, the urethane resin aqueous dispersions, thickeners, crosslinking agents, and pigments shown in the table were mixed in the same manner as aqueous urethane resin composition 1 to prepare various aqueous (or comparative aqueous) urethane resin compositions.

[0174] The obtained aqueous urethane resin composition was applied to the same base fabric as in Example 1, and the same processing was performed. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.

[0175] [Examples 10 and 11]

[0176] The coating amount of the coating material applied to the base fabric was set to 6 g / m 2 , 15g / m 2 Except for this, the same operation as in Example 7 was carried out. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.

[0177] [Example 12]

[0178] The polyethylene terephthalate fiber with a total fineness of 550 dtex, 140 monofilaments, and a tensile strength of 8.0 cN / dtex was warped in a twist-free and glue-free form, and the weft yarn used the same yarn and was woven into a plain weave using a water jet loom. After refining and shaping, the base fabric weight was 243 g / m 2 As in Example 1, a urethane resin aqueous dispersion 7 was prepared to a concentration of 11 g / m 2 The base fabric was coated here in the manner of , and the same processing as in Example 1 was performed. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.

[0179] [Comparative Examples 2 and 3]

[0180] The coating amount of the coating material applied to the base fabric was set to 3 g / m 2 , 20g / m 2 (Solid content) Except for this, the operation was carried out in the same manner as in Example 7. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.

[0181] [Table 1]

[0182]

[0183] [Table 2]

[0184]

[0185] [Table 3]

[0186]

[0187] Industrial Applicability

[0188] The base fabric for airbags of the present invention is a base fabric having high air tightness, good storage property and light weight, and can be suitably used for airbags having high storage property, light weight and low air permeability.

Claims

1. A base fabric for an airbag, comprising a base fabric and a cured product of an aqueous urethane resin composition applied to at least one surface of the base fabric, characterized in that: The aqueous urethane resin composition comprises a urethane resin obtained by reacting (d) a polyamine having two or more amino groups and / or imino groups with an isocyanate group-terminated prepolymer, wherein the isocyanate group-terminated prepolymer is obtained by reacting (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (c) a compound having an anionic hydrophilic group and at least two active hydrogen atoms as essential components. 5g / m 2 ~15g / m 2 A cured product of the aqueous urethane resin composition is applied.

2. The base fabric for an air bag according to claim 1, wherein: The (b) branched polycarbonate diol has a structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms.

3. The base fabric for an air bag according to claim 1 or 2, wherein: The (b) branched polycarbonate diol has a structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms and a structural unit derived from a diol having a linear structure and having 3 to 10 carbon atoms.

4. The base fabric for an air bag according to claim 1 or 2, wherein: The aqueous urethane resin composition comprises a urethane resin, wherein the urethane resin is obtained by reacting the (d) with an isocyanate-terminated prepolymer, wherein the isocyanate-terminated prepolymer is obtained by reacting (a), (b) and (c) with (e) a trivalent or higher alcohol as an essential component.

5. The base fabric for an air bag according to claim 1 or 2, wherein: The slip resistance of the base fabric for the airbag is 1000N to 2500N.

6. The base fabric for an air bag according to claim 1 or 2, wherein: The air permeability of the base fabric for airbags under a pressure difference of 100 kPa is 0.01 l / cm 2 / min or less.

7. The base fabric for an air bag according to claim 1 or 2, wherein: The base fabric for airbags is composed of raw yarn with a fineness of 200 dtex to 800 dtex.

8. The base fabric for an air bag according to claim 1 or 2, wherein: The fibers constituting the base fabric are polyethylene terephthalate fibers or polyhexamethylene adipamide fibers.

9. The base fabric for an air bag according to claim 1 or 2, wherein: The tensile strength of the fibers constituting the base fabric is 7.5 cN / dtex to 11.5 cN / dtex.

10. The base fabric for an air bag according to claim 1 or 2, wherein: The weight of the remaining amount after removing the cured product of the aqueous urethane resin composition is 150 g / m 2 ~300g / m 2 .

Citation Information

Patent Citations

  • Base fabric for air bag and air bag

    JP2009062643A

  • Base cloth for airbag, airbag composed of the same, and manufacturing method of the same

    JP2011168131A